Fano resonance of waves in periodic slabs - Ptitsyna, N.; Shipman, S.P.; Venakides, S. (2008 12th International Conference on Mathematical Methods in Electromagnetic Theory, 2008)
We investigate Fano-type anomalous transmission of energy of plane waves across lossless slab scatterers with periodic structure in the presence of non-robust guided modes. Our approach is based on rigorous analytic perturbation of the scattering problem near a guided mode and applies to very general structures, continuous and discrete.